Experiences on Necrotizing Enterocolitis in Neonates and Young Infants in North Sulawesi - Muzief Munir (Paediatrica Indonesiana, 1984)
Since the predisposing factors of necrotizing enterocolitis in newborns and young infants in developed. and developing countries are totally different, the evaluation of epidemiological, clinical and management problems of 20 of our newborn cases and 3 young infants was conducted. It is evident that gastroenteritis and severe pulmonal infections are indeed the most important risk factors in developing necrotizing enterocolitis in our cases. Rooming-in and breast feeding practices reduce sharply the incidences of diarrheal diseases in newborn infants, and in turn, cause a decline in the prevalent rate of necrotizing enterocolitis.